Pembinaan Karakter Siswa melalui Program Gema Haji dan Kelasku ‎Mushollaku di Gugus 3 Kalijaga, Lombok Timur - M. Pajri; Akh. Bayu Rifki; M. Habiburrahman; Ismail Ismail (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
This study aims to describe strategies for fostering student character through the Gema Haji and Kelasku Mushollaku programs and to analyze their implications for student character in Cluster 3 of Kalijaga. The study employs a descriptive qualitative approach, utilizing data collection techniques such as observation, interviews, and documentation at SD Negeri 2 Kalijaga and SD Islam Al-Barokah Kalijaga Tengah. The research findings indicate that character-building strategies are implemented through setting a good example, fostering habits, maintaining discipline, and creating a religious atmosphere in the classroom. This program fosters students’ religious character, discipline, responsibility, environmental awareness, cooperation, and independence. These findings confirm that Gema Haji and Kelasku Mushollaku are effective as models for character development based on school culture and religious habit formation.